Estrutura cristalina e refinamento de deformação em sais de ácido piromelítico - Leonardo Humberto Rezende dos Santos (2012)
Four organic salts derived of 1,2,4,5-benzenetetracarboxylic acid (pyromellitic acid) have been synthesized: bis(3-aminopyridinium) 1,4-dihydrogen 1,2,4,5- benzenetetracarboxylate tetrahydrate (1), bis(3-carboxyphenilammonium) 1,4- dihydrogen 1,2,4,5-benzenetetracarboxylate dihydrate (2), bis(4-carboxyphenilammonium) 1,4-dihydrogen 1,2,4,5-benzenetetracarboxylate (3) andbis(3-carboxypyridinium) 1,4-dihydrogen 1,2,4,5-benzenetetracarboxylate (4a,b). Crystal structures of all compounds were determined by single-crystal X-ray diffraction at 120 K. Compound 1 crystallizes in the space group P21/c while compounds 2 and 3 crystallize in the group Pi. Compound 4 has been observed in two polymorphic formswhich crystallize in the space groups Pi (4a) and P21/c (4b). Intermolecular hydrogen bonds are particularly important to building uncommon supramolecular arrays. Additionally, crystallographically asymmetric intramolecular short O-H···O hydrogen bonds are observed in 2, 4a and 4b. The O···O distances are 2.387(1), 2.423(1) and2.385(1) A respectively. 4a also presents an intermolecular short O-H···O hydrogen bond in which the O···O distance is 2.513(2) A. Electron deformation refinement has been carried out in 4a by using multipolar atomic nucleus-centered deformation functions and the electron density distribution has been interpreted using Quantum Theory of Atoms in Molecules, which has given evidence of partly covalent character ofshort hydrogen bonds in this polymorphic modification